2021
DOI: 10.1007/s40620-020-00908-9
|View full text |Cite
|
Sign up to set email alerts
|

Calciphylaxis in end-stage kidney disease: outcome data from the United Kingdom Calciphylaxis Study

Abstract: Background and aims Calciphylaxis is a rare condition associated with very high mortality in patients with end-stage kidney disease. Data from country-based registries have been an invaluable resource for a better understanding of the natural history and management for this condition. This study aimed to investigate the current management strategies and outcomes of patients enrolled in the United Kingdom Calciphylaxis study (UKCS). Methods The study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 34 publications
3
24
4
Order By: Relevance
“…Several studies have reported 1-year mortality rates in patients with calciphylaxis at 40–50% or higher [ 11–14 ]. A recent analysis of the UK Calciphylaxis Registry reported a 1-year mortality rate of 67% versus 10% in patients receiving dialysis without calciphylaxis [ 10 ]. Patients with calciphylaxis also have a high morbidity burden and poor quality of life (QoL) related to painful wounds, ambulatory difficulties and frequent hospitalizations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported 1-year mortality rates in patients with calciphylaxis at 40–50% or higher [ 11–14 ]. A recent analysis of the UK Calciphylaxis Registry reported a 1-year mortality rate of 67% versus 10% in patients receiving dialysis without calciphylaxis [ 10 ]. Patients with calciphylaxis also have a high morbidity burden and poor quality of life (QoL) related to painful wounds, ambulatory difficulties and frequent hospitalizations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with calciphylaxis also have increased susceptibility to wound infections, which are ultimately responsible for approximately 50% of mortality associated with calciphylaxis [11,12]. Calciphylaxis in patients with ESKD can be a life-threatening condition, with 1-year mortality rates exceeding 45% [9,11,13,14], and calciphylaxis independently increases the risk of death by up to 8-fold [5,6,14].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the majority of calciphylaxis lesions are highly inflammatory chronic wounds, with a local ischemic component that inhibits the progression from the inflammatory to the proliferative phase. Given the severity of the ulcers and the co-morbidities that are common in patients with calciphylaxis, complete wound healing may be delayed and complicated by superinfection, sepsis, and death [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations